PENGARUH SISTEM INFORMASI AKUNTANSI MANAJEMEN, TOTAL QUALITY MANAGEMENT, DAN DISIPLIN KERJA TERHADAP PENGUKURAN KINERJA KARYAWAN PADA PERUSAHAAN PERBANKAN DI RANGKASBITUNG TAHUN 2024 - M. Luthfan Hidayat; Siti Mudawanah (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2024)
This research is quantitative research and aims to determine the influence of Management Accounting Information Systems, Total Quality Management, and Work Discipline on Employee Performance Measurement at Banking companies in Rangkasbitung. The sampling technique used in this research was a saturated sample, and a sample of 325 employees was obtained and the data collection technique was used with primary data obtained from the results of distributing questionnaires. The results of the research that has been carried out show that the Management Accounting Information System does not partially have a significant positive effect on measuring employee performance. Total quality management partially influences employee performance, and work discipline partially has no significant influence on employee performance.